Gestion Et Dispensation Des Medicaments Antiretroviraux A Brazzaville : Cas Du Centre De Traitement Ambulatoire (Cta) Et De La Pharmacie Du Centre Hospitalier Et Universitaire De Brazzaville (Chub) - Bruno, Mokoko Jean; Gandzaley, Ondélé; Antoine, Abena Ange; Mahamboula, Diafouka MerlinNsondé (European Scientific Journal, ESJ, 2018)
In Congo, the distribution of generic drugs including ARVs (Antiretrovirals) is done through dispensing sites. This paper focuses on describing the management, delivery, and supply of ARVs at two sites in Brazzaville, and thus contributes to improving the management of HIVpositive patients. This is a cross-sectional, observational, descriptive, and analytical study of 3,473 patients registered at the Hospital and University Hospital Pharmacy (CHUB) and Ambulatory Treatment Center (CTA) during the period from 1st January to December 31, 2010. The data were collected using medical records, prescriptions, inventory sheets, purchase orders, delivery notes of the Congolaise of Essential Medicines Generic (COMEG), and informal interview with the heads of dispensing units. Of the 3473 patients registered, there were 1412 men (40.65%) and 2061 women (59.34%). A sex ratio of 0.68 at the pharmacy of CHUB 13427 boxes of ARVs was ordered unlike the CTA where this number was 30810 boxes of ARV. The COMEG delivered to the CTA 28,667 boxes of ARVs (93.04%) dispensing 18,994 boxes. Half of the ARVs dispensed were the triple combinations (56,48%). At the CHUB pharmacy, COMEG delivered 15,371 boxes of ARVs, of which 28.16% is also a triple therapy. The analysis of the system revealed a poor estimate of needs because the dispensing and management of these drugs does not conform to the active queue.